The final hour: Coach-athlete interactions immediately prior to performance in basketball - Fletcher, S. (2006)
Pre-competitive preparations in elite sport have been shown to be important to performance. In particular, mental preparation and mental readiness have been shown to be important determinants of successful performance. For example, Orlick and Partington (1988) highlighted that mental preparation in Olympic athletes was perceived to be important to successful performance. In the search for understanding of performance excellence researchers (e.g., Durand-Bush & Salmela, 2002, Mahoney & Avener, 1977; McCaffey & Orlick, 1989; Orlick & Partington) have highlighted the role of the coach in the development and maintenance of elite performance. Above all, the coach has been found to be a critical element of performance and has been perceived to be influential to athletic performance in both a positive or negative manner. In addition, researchers have highlighted that coaches and the coaching processes/practices that they adopt are influential in constructing a performance environment that could aid or hinder athletes preparing for and performing in competition (Côté & Sedgwick, 2003). In particular, coach-athlete interactions immediately prior to performance are suggested to be an important determinant of mental preparation and performance (Gould, Guinan, Greenleaf, Medbery, & Peterson, 1999). There is limited information, however, on coach-athlete interactions immediately prior to performance and the influence on mental preparation and performance. In this thesis, I investigated coach-athlete interactions immediately prior to performance in semi-elite basketball teams. The participants in the study were four single sex (2 male and 2 female) coach-athlete dyads competing in Australian Basketball Association (ABA) conferences. I applied a multi-method study comprising the following four linked phases for each dyad. Phase 1, involved a semi-structured interview with the coach focused on their coaching intentions/practices immediately prior to a game. Phase 2, involved observation of training and of the final hour prior to a game. Phase 3, involved a semi-structured interview with a targeted player on their perceptions of the coach prior to performance. Phase 4, involved a Verbal Cued Stimulated Recall Interview (VCSRI) with the coach. The VCSRI was focused on the coaches` explanations and reflections on their actions and communications immediately prior to the game recorded in Phase 2. The data were analysed using ground theory methods and constant comparative analysis. Overall, I found that the four coaches aimed to construct a pre-performance environment that fostered players` physical preparation, mental preparations and readiness, and reinforced the game plan and tactics practiced during the week. In addition, coaches were also found to spend time focused on personal preparation in order to ready themselves mentally for their role in the pre-game period and in the game. Coaches suggested that a key aspect of mental preparation was the use of pregame routines. All four coaches proposed that pre-game routines either individual or team based aided their own and athletes` mental preparation for competition. In particular, pre-game routines facilitated athletes into a game centred focus and narrowed their attention onto the game, the team, and their individual role within the team. Coaches` were found to have structured the pre-game preparations differently depending on the preferences of the team or their own preferred coaching style, giving players more or less free time to complete their own pre-game routines. A number of external factors mediated the structure and style of the pre-game routines. These factors included the time of the season, the level of development, player experience, and the coaches` assessment of player preparations prior to the game. To aid players` mental preparation coaches were found to apply a combination of motivational strategies (praise, positive reinforcement, and confidence). In particular, coaches stated that they used individual interactions to focus players and aid the players in mentally preparing for the game. The coaches achieved this through structured warm-ups, individual interactions and individual coaching, motivational strategies, player assessment, and the pre-game talk. I also found that coaches monitored their players throughout the preperformance period and used their background knowledge of the players` personality, preferred coaching style, game state, current form, and body language to assess the progress to assess the mental readiness of players before a match. Coaches applied this mental framework to players` pre-game preparations to assess their progress. If coaches perceived one of their players to be unprepared they would take them aside and speak individually to the player and try to refocus them by showing confidence in their ability, praise, encouragement, and individual goal setting. A key finding related to the players perception of their coach. The majority of players perceived their coaching to be a positive influence on their preparations, a source of motivation, and confidence. Players`, however, did not always agree with their coach`s decisions and style of coaching before a game. Specifically, players` were found to have perceived coaches as organisers and facilitators, whom aided them to reach their optimal preparation for performance. The interactions between coach and player were found to differ depending on several mediating factors. The mediating factors included players` level of development, time of the season, player`s form, opposition, the teams place on the ladder, and players` preferred coaching style. The mediating factors determined the content and focus of the pre-game talk and the interactions with players. The results depicted in the Pre-Performance Coaching Model (VRICPP). The VRICPP model depicts the processes and interacting factors that influence coaches and athletes during the pre-game preparation, in particular mental preparation and performance. The model highlights the interaction between coach and player personal variables, the coach-athlete relationship, mediating factors, mental framework of players, coach intervention, preparation, and performance. In conclusion, coach-athlete interactions immediately prior to performance are focused on the optimal mental and physical preparation, player mental readiness and game focus, positive reinforcement of team plan/strategies, team cohesion, and coach preparation. Coach-athlete interactions were focused on motivation, confidence, positive reinforcement, and game focus. Importantly, coaches needed to be aware of all aspects of their players` behaviour and personality in order to be an effective coach. Furthermore, coaches` interventions were a compromise between players` needs, what was best for the team, and what coaches perceived to be best for the player. In addition, a key aspect of coach-athlete interactions before a game was open and honest communication. Coaches and players needed to be able to openly communicate important information under pressure and with limited time available. The results from this study have important implications for coaches and athletes. In particular, knowledge of players preferred coaching style and knowledge of players` form, mental state, and preparation before matches are important skills for elite coaches to know. In addition, coaches need to know how to effectively intervene with each player in order to aid players` mental and physical readiness.